Nigerian information and communications technology handbook, ICT 2005 (Lagos, Nigeria : Compumetrics Solutions, 2005)
The book focuses on ICT and its impact on the economy of Nigeria by presenting sectorial findings coving agriculture and forestry, arts and entertainment, automobile and tyres, banking and finance, education as well as engineering and building.
oif 15/07/14
Ref
Keywords: Communication and technology; Information technology; Information technology; Telecommunication